ax^2+bx+c=0 subtract c from both sides
ax^2 + bx = -c divide through by a
x^2 + (b/a)x = -c/a take (1/2) of (a/b) = b / [2a].....square this = b^2/[4a^2]...
add it to both sides
x^2 + (b/a)x + b^2/[4a^2] = -c/a + b^2/[4a^2]
Factor the left side.....get a common denominator on the right
( x + b/[2a] )^2 = [ b^2 - 4ac] / [4a^2]
Take both square roots
x + b/[2a] = ± √ ( [ b^2 - 4ac] / [4a^2] )
x + b/[2a] = ± √ ( [ b^2 - 4ac] / [2a] )
Subtract b/[2a] from both sides
x = ± √ ( [ b^2 - 4ac] / [2a] ) - b/[2a]
x = ( -b ± √ ( [ b^2 - 4ac] ) / [ 2a ]
Voila!!!!!......this is the Quadratic Formula.....